PENELUSURAN IDE, EKSPEKTASI MAHASISWA DAN DOSEN PROGRAM STUDI JINAYAH TERHADAP IKLIM PEMBELAJARAN - Hadi, Abdul (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Expectation is a trigger factor for a person's activities in life. If someone finds reality that is in accordance with his expectations, it will encourage enthusiasm in life. In addition to ideas, this is understood as something that comes out of someone's mind that provides various concepts to overcome and enhance the values ​​of life for themselves and others. Associated with the learning process, ideas and expectations are intended to explore within the scope of the process of improving the quality of learning undertaken. The search for ideas and expectations of students, and lecturers on the learning model that should be applied will be very useful to find a common thread of problems that occur in the learning model that has been used so far that the quality of the results does not meet expectations to the fullest. This article explored integrate ideas and concrete steps for the formulation of learning models that meet people's expectations indirectly, because basically between students and lecturers are two elements that need each other in the context of scientific transformation.